The Real Deal: Using Authentic Assessment to Promote Student Engagement in the First and Second Years of a Regional Law Program - Caroline Hart; Sara Hammer; Pauline Collins; Toni Chardon (Legal Education Review)
Labour law is an academic discipline which overtly touches upon a number of other disciplines such as labour history, industrial relations and economics. This article argues that there are pedagogical justifications for incorporating contextual socio-legal material into the teaching of labour law. The incorporation of such content fosters deep learning and also equips students to make thoughtful, informed choices in their working lives and in their roles as citizens and consumers. It is thus in keeping with universities’ obligations to concern themselves with advanced learning, the development of intellectual independence and acceptance of a role as conscience and critic of society. The article also reports on a survey of New Zealand and Australian labour law lecturers, in both law and business schools, on their use of socio-legal material in teaching labour law in to undergraduates. The survey findings suggest that while a number of New Zealand and Australian law lecturers consider socio-legal material very important and incorporate it into their teaching, not all do. Following this, some methods by which lecturers may incorporate socio-legal material into their teaching are discussed. It is concluded that if it is indeed very important that students should learn to see labour law in its socio-legal context then this should be formally stated as a course objective, interwoven into the curriculum and reflected in assessment. At the same time care must be taken in terms of finding an optimal balance between socio-legal context and black letter law.